The Effect of Tourism Development on Land Conversion in East Lombok Regency - Yudita, Anisa (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Tourism is one of promising aspects which is growing rapidly today. Indoensia is the fourth tourism destination in South East Asia. The data from Government Tourism Office found that there has been an increasing number of visitors to Indonesia in the last three years.This certainly requires the development of supporting aspects, such as roads, transportation, facilities, accommodation and some other supporting aspects of tourismobjects.This research was aimed to know the effect of tourism development on land conversion in the coastal area of East Lombok Regency. This study employed a mixed method research (qualitative and quantitative). The reason of using this research method was to obtain the information that meet this research’s purposes. This research cllected primary and secondary data which were related to tourism and lad conversion. The data was obtained from field observation, interview, literature review, documentation, image analysis and additional information from related agencies. The result of this research revealed very slow development of tourism objects in coastal area of East Lombok Regency. Consequently, it resulted on very few land conversion in the coastal area of East Lombok due to a slow tourism development.